The no asshole rule building a civilized workplace and surviving one that isn't - Sutton, Robert I. (New York Hachette Audio, 2007)
This groundbreaking audiobook is more than just a reflection on the issue of social friction among corporate colleagues. Dr. Sutton sheds real analytical light on how this ongoing problem ruins morale, lowers productivity, and can truly devastate a company's culture. Sutton not only confronts this issue directly, but also provides extensive stragegies and insights into how your company can pinpoint and eliminate this problem"
Featuring a conversation with the author"--Container.
Keywords: Organizational behavior